A COMMON FIXED POINT THEOREM IN MENGER SPACE USING PROPERTY E. A. AND IMPLICIT RELATION - Manro, Saurabh (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
In this paper, we obtain some results on fixed points in menger space using property E.A. recently introduced by Amari and Moutawakil [1]. Our results are the Menger version of some fixed point theorems for self mappings on different metric spaces. Key words: Menger space, property E.A., Common fixed point.